Influence of social distancing on family relations in the Federal District - Augusto Martins Paiva, Alberto (2022)
With the new coronavirus, changes in the way of living among individuals of the same family became evident with the worsening of the pandemic, especially in Brazil. This study aims to analyze the perception of individuals about personal family relationships during the experience of social isolation due to COVID-19. This is an exploratory and descriptive research, with a quali-quantitative approach carried out with individuals who have experienced social isolation. Twenty-five subjects between the ages of 18 and 25 participated in the research. As a data construction technique, we chose the online questionnaire produced in the Survio® platform. The results of the research indicated that the participants showed a worsening of relationships between individuals from the same family, due to the prolonged period of coexistence because of social isolation and with restrictions on leaving their homes. Keywords: Covid-19; Family conflict; Social isolation.